Effects of some management factors (Housing condition and watering regimen) on blood parameters of desert goats - Mohammed Alhadi Ebahiem; Intisar Alnour Ismail; Salah Abulgabar Salah Bukhari; Suleiman Eshag Abdalla Mohamed; Salah Basar Hammad Dahia; Adam Jumaa Hamid Hamdoun; Jumaa Barram Jadalla (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
This study aimed to assess the effects of housing condition and watering regimen on some blood parameters during the period May 2018- February 2019. Desert goat Package Cell Volume% (PCV %) were highest during January, February and lowest during May, and August. Goats had the highest (P<0.001) blood Hemoglobin (Hb%) during May and July with very slight fluctuations throughout the seven months of the experimental period. Goats under shade had comparatively higher PCV% and slightly lower Hb% in comparison with those under direct sunlight. Plasma Calcium was low during February and January and rose during December with higher levels during May, June and July. Goat plasma phosphorus concentrations followed an opposite picture being highest (P<0.01) during October, December, and February and lowest (P<0.01) during other months. Plasma Calcium (Ca) and Phosphorus (P) concentrations were slightly (P>0.05) higher for goats under shade compared with those under direct sunlight. The main effects of months on blood metabolites were highly significant (P<0.01). The highest goat blood protein was during, June-July and lowest (P<0.01) during other months. Goat blood albumen levels were highest (P<0.001) for August- September- October and lowest for January- February whereas blood glucose levels were highest (P<0.01) during January- February and with very slight fluctuations throughout the seven months of the experimental period. Blood protein, blood albumin and blood glucose levels were relatively higher (P>0.05) for goats under shade compared with those under direct sunlight. Goats watered everyday had slightly lower blood protein and albumin and slightly higher blood glucose in comparison with goats watered every other day.